Heterotopic and Funerary Spaces: Martin McDonagh’s A Skull in Connemara - Jordan, Eamonn (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Traditionally, the west of Ireland has been framed more often than not as a potential pastoral space, one of refuge, sanctuary and belonging, as well as a place where individuals can reflect, mature and heal. Pastoral spaces are also ones of grief, where death is accommodated and eulogized (See Gifford 7-8). Pastoral is often aligned with an utopian trope. Michel Foucault’s ideas on heterotopic spaces offer a very apposite addition to discussions on the pastoral and they also link in with the notion of funerary practices, allowing one to interlink the transcendent, and its opposite, the sanctified and the de-sanctified, the notionally sociologically real and the imaginary. Writing in 1967, Foucault speaks of the fact that “contemporary space is perhaps still not entirely de-sanctified (apparently unlike time, it would seem, which was detached from the sacred in the nineteenth century)” and that oppositions between “family space and social space, between cultural space and useful space, between the space of leisure and that of work” . . . remain inviolable,” as that inviolability is still “nurtured by the hidden presence of the sacred” (23). While pastoral spaces notionally can be some of the better examples of idyllic sanctified spaces, that sense of “inviolable” divisions seems to no longer stand in relation to McDonagh, as he is both evoking but also disputing that “hidden sense of the sacred” in A Skull in Connemara (1997).